2015
DOI: 10.5539/jas.v7n6p137
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Economic Performance of Broiler Chickens Fed on Graded Levels of Canola Meal with or without Multi-Enzyme Supplementation

Abstract: Canola meal (CM) is commonly used in poultry diets; however, its use is limited due to anti-nutritive factors. Therefore, this study was conducted to evaluate the effects of feeding various levels of canola meal (CM) with or without multi-enzyme supplement on broiler chickens. Four levels of CM (0, 5, 10 and 20%) were used with or without multi-enzyme (0 or 300 g/ton of diet) in a factorial design 4 × 2 in 8 dietary combinations. During the experimental period (0-42 d of age), inclusion of CM at a level of 5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
7
9
0
Order By: Relevance
“…These results are contrary with results obtained by Ahmad et al (2007); who reported that HI antibody titer against ND virus was lowest in diets containing 10% CM, whereas, it was highest in those having 15% CM. In another respect, CM at 30% and 60% replacement level did not cause significant effect on the relative weight of lymphoid organs compared to the control which agree with results reported by Ahmed et al (2015) when they fed broilers diets contained 5, 10 and 20% CM. Also, the present results are compatible with the results of Ashnie et al (2015) where, they did not found a significant differences of relative spleen weights among broilers fed diets contained 0, 7.5 and 15% CM while, the broilers fed diets contained 22.5 and 30% CM showed a significant increase of relative weights of spleen compared to the control group which was contrary with our results.…”
Section: Immune Response and Lymphoid Organssupporting
confidence: 88%
“…These results are contrary with results obtained by Ahmad et al (2007); who reported that HI antibody titer against ND virus was lowest in diets containing 10% CM, whereas, it was highest in those having 15% CM. In another respect, CM at 30% and 60% replacement level did not cause significant effect on the relative weight of lymphoid organs compared to the control which agree with results reported by Ahmed et al (2015) when they fed broilers diets contained 5, 10 and 20% CM. Also, the present results are compatible with the results of Ashnie et al (2015) where, they did not found a significant differences of relative spleen weights among broilers fed diets contained 0, 7.5 and 15% CM while, the broilers fed diets contained 22.5 and 30% CM showed a significant increase of relative weights of spleen compared to the control group which was contrary with our results.…”
Section: Immune Response and Lymphoid Organssupporting
confidence: 88%
“…Guar meal has been proved as a cheaper feed ingredient than cotton seed cake (CSC) and replacing CSC with GM helped in economical ration formulation without any detrimental effects on growth performance in animals (Sharif et al, 2014). Furthermore, enzyme supplementation in GM diets has shown positive effects on dressing percentage in broilers (Ahmed et al, 2015). Studies involving a dietary inclusion of guar in different avian species are summarized in Table 5.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 99%
“…Moreover, enzyme supplementation in GM diets has shown positive effects on serum high-density lipoprotein (HDL) in broilers (Ahmed et al, 2015). Supplementation of 15% GM with or without enzyme supplementation and 15% fermented toasted guar meal (FTGM) found to be most effective in reduction of serum cholesterol and glucose level.…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fibre has been reported to reduce protein and energy digestibility resulting in poor growth performance in chickens (Ahmed et al, 2015 ). Consequently, the potential of CM as a replacement for soybean products in diets of improved poultry species is limited by the negative physiological effects of these ANFs, as reported for quails (Karayagız and Bulbul, 2015 ; Mnisi and Mlambo, 2017 ) and broilers (Gopinger et al, 2014 ; Ahmed et al, 2015 ). A decline in feed intake and body weight was also observed by Woyengo et al ( 2011 ) in broilers fed on diets containing graded levels (0 to 40%) of CM.…”
Section: Introductionmentioning
confidence: 99%